2014
DOI: 10.1007/s12013-014-0161-8
|View full text |Cite
|
Sign up to set email alerts
|

The R219K Polymorphism on ATP-Binding Cassette Transporter A1 Gene is Associated with Coronary Heart Disease Risk in Asia Population: Evidence from a Meta-Analysis

Abstract: A number of case-control studies have been conducted to investigate the relationship between the ATP-binding cassette transporter A1 (ABCA1) gene polymorphisms and risk of coronary heart disease (CHD). However, the results have been inconclusive. The purpose of the present study is to investigate whether this polymorphism confers significant susceptibility to CHD using a meta-analysis. We conducted searches of the published literature in PubMed, Embase, and CBM databases. 13 studies were included in our meta-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…A lot of supposed glycosylated sites have been reported within this loop, and a lot of potential losses in the variants that induce the function determining the level of HDL-C have been suggested [22]. Meanwhile, some other studies even suggest that ABCA1 219K allele modified the risk of CHD without important modification of plasma HDL-C level [26]. Either way, given that based on the functional analysis using SIFT and PolyPhen, this R219K variation of ABCA1 is suggested not to be functional in itself, it could rather be causal…”
Section: Resultsmentioning
confidence: 99%
“…A lot of supposed glycosylated sites have been reported within this loop, and a lot of potential losses in the variants that induce the function determining the level of HDL-C have been suggested [22]. Meanwhile, some other studies even suggest that ABCA1 219K allele modified the risk of CHD without important modification of plasma HDL-C level [26]. Either way, given that based on the functional analysis using SIFT and PolyPhen, this R219K variation of ABCA1 is suggested not to be functional in itself, it could rather be causal…”
Section: Resultsmentioning
confidence: 99%
“…ABCA1 encodes an important protein that facilitates the formation of HDL-C and regulates the efflux of lipids from peripheral cells into lipid-poor ApoA1 particles, stimulating reverse cholesterol transport. [ 30 ] The association between the ABCA1 gene polymorphisms and CAD has been the focus for many studies [ 31 33 ]. The rs2230806 is the most common polymorphism of ABCA1 ; the possible role of rs2230806 in cardiovascular diseases is still debatable as numerous studies have reported divergent results [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the R219K (rs2230806) gene polymorphism, which has been related to CHD risk [7], ischemic stroke [8], TGs and HDL-C concentrations [9] was evaluated by Liu et al [10] in meta-analysis that included 13 studies with 11,678 individuals. Significant association between R219K gene polymorphism and increased CHD risk was found in total population analyses in all 4 genetic comparison models.…”
Section: Discussionmentioning
confidence: 99%